(untitled) (Scientific journal of the Fergana State University, 2023)
The structural changes are going on in our Republic. A structure includes connection with elements and their inter-influence of the structure. That’s why, changing the structure makes change the society. In the article, the strategy of activity of development as the whole system of intercommunication, links and relations between the elements is researched.